Orbital engineering: photoactivation of an organofunctionalized polyoxotungstate - Newton, Graham; Oshio, Hiroki; Cameron, Jamie; Fujimoto, Satomi; Kastner, Katharina; Wei, Rong Jia; Robinson, David; Sans, Victor (Wiley, 2017)
Tungsten-based polyoxometalates (POMs) are employed as UV-driven photo-catalysts for a range of organic transformations. Their photoactivity is dependent on electronic transitions between frontier orbitals, and thus manipulation of orbital energy levels provides a promising means of extending their utility into the visible regime. Here, an organic-inorganic hybrid polyoxometalate, K₆[P₂2W₁₇O₅₇(PO₅H₅C₇)₂]·6C₄H₉NO, was found to exhibit enhanced redox behavior and photochemistry compared to its purely inorganic counterparts. Hybridization with electron withdrawing moieties was shown to modify the frontier orbital energy levels and reduce the HOMO-LUMO gap, leading to direct visible-light photoactivation of the hybrid, and establishing a simple, cheap and effective approach to the generation of visible-light-activated hybrid nanomaterials